Mechanical Performance of Asphalt Mixture Containing Cup Lump Rubber - Norfazira, Mohd Azahar; Norhidayah, Abdul Hassan; Putra Jaya, Ramadhansyah; Hasanan, Md. Nor; Mohd Khairul Idham, Mohd Satar; Nordiana, Mashros; Azman, Mohamed (Penerbit Universiti Teknologi Malaysia, 2019)
The use of cup lump rubber as an additive in asphalt binder has recently become the main interest of the paving industry. The innovation helps to increase the natural rubber consumption and stabilize the rubber price. This study evaluates the mechanical performance of cup lump rubber modified asphalt (CMA) mixture in terms of resilient modulus, dynamic creep and indirect tensile strength under aging conditions. The CMA mixture was prepared using dense-graded Marshall-designed mix and the observed behavior was compared with that of conventional mixture. From the results, both mixtures passed the volumetric properties as accordance to Malaysian Public Work Department (PWD) specification. A comparable result was obtained for stability and indirect tensile strength. The addition of 5% cup lump rubber provides better resistance against permanent deformation through the enhanced properties of resilient modulus and dynamic creep by 27% and 126% respectively under unaged condition. Furthermore, lower permanent strain was also observed for CMA compared to conventional mixture.